Gamification Through Genially Enhanced Generation Alpha in-Class Chinese Language Learning Engagement - Sean Patrick Kang; Mochammad Aozora Isya’ Alghifari (Nusantara Science and Technology Proceedings, 2024)
The 21st Century symbolises rapid digitalisation since The Industrial Revolution (IR) 4.0., remote learning during the pandemic, and innovations towards Society 5.0. China’s initiatives in economic development projects around the world impact the higher demand for learning Mandarin. The researchers acknowledged the importance of invigorating Mandarin language learning in light of the 21st century needs. The Chinese as a Foreign Language (CFL) students are Generation Alpha (Gen-A) as digital natives with full digital exposure since early childhood. Further, they have shorter attention spans and prefer learning interactively in chunks. The researcher realises the urgency for maintaining an engaging yet effective lesson with gamification and the importance of learning engagement in developing students’ linguistic skills. This qualitative study investigates the enhancement of learning engagement of grade 1 CFL students through the implementation of Genially as the gamification approach. The researchers and parallel teachers periodically noted phenomena during the implementation with field notes. Then, compile and analyse the notes with thematic analysis. The researchers discovered impressive outcomes in students who were behaviourally, affectively, and cognitively engaged. They proactively inquired about the lesson which showed higher curiosity and engagement levels. They exhibited excitement and motivation by voluntarily raising their hands to give responses. Overall, implementing Genially on Gen-A CFL students enhances greater learning engagement in three aspects. The researchers believe this study can be the vantage point for future research and development in foreign language learning other than English.